PENGARUH MODAL KERJA TERHADAP LIKUIDITAS PADA KEGIATAN USAHA PERDAGANGAN - Sofiah Nur Iradawati (UMSurabaya Publishing, 2011)
Working capital is one of important factors in conjunction with the company's day-to-day activities, as well as indicate the level of security (margin of safety) for the creditors, especially short-term creditors. The importance of working capital for the company as proposed by S. Munawir (1997; 116) as follows: